PENGARUH CURRENT RATIO DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON ASSETS PADA PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK PERIODE 2013 – 2022 - Kurniawati, Melinda; Tita Amalya, Neneng (Journal of Research and Publication Innovation, 2024)
This research aims to determine whether or not there is an influence of the Current Ratio on Return On Assets and Total Assets Turnover on Return On Assets, either partially or simultaneously. The object of this research is PT Industri Jamu Dan Farmasi Sido Muncul Tbk for the 2013-2022 period. The data used in this research is secondary data. Using descriptive research methods and the data is quantitative. The variables used are Current Ratio (X1) and Total Assets Turnover (X2) to Return On Assets (Y). In the partial test results, the Current Ratio shows that there is a partial and significant influence on Return On Assets. With the results of the calculated t value > t table and significant < 0.05, namely: (-2.156 > 2.306) and (0.068 < 0.05). The partial research results of Total Asset Turnover show that there is no influence and is not significant on Return On Assets. With the results of the calculated t value < t table and not significant > 0.05, namely: (1.205 < 2.306) and (0.267 > 0.05). The results of hypothesis testing simultaneously have a significant effect between the Current Ratio and Total Asset Turnover on Return On Assets. With the results of f count > f table and significance < 0.05, namely: (9,275 > 4,350) and (0.011 < 0.05) The results of the Adjusted R Squere coefficient of determination test are 0.648 or 64.8%, which means that the contribution made by Current Ratio and Total Assets Turnover on Return On Assets reached 64.8% while the remaining 35.2% was influenced by other variables not explained in this research.